Penerapan Metode Advanced Encryption Standard (AES) Pada Keamanan Password Server Cloud Universitas Budi Darma - Wahyudi Wahyudi (STMIK Budi Darma, 2022)
Today's technological developments are increasingly rapid and easy to find and apply in various aspects of personal, social, cultural and business life which greatly impact changes in human attitudes and behavior. The things that are expected from technological developments are certainly to facilitate human work in assisting conventional activities which are now being replaced with technological conveniences that continue to develop. However, along with the development of technology, there is a negative side that could encourage people to carry out various kinds of criminal threats that can attack when the software development process occurs, including theft and manipulation of software data that is being developed which causes material losses and financial. One effort to reduce the level of threat risk is by implementing cryptography. Cryptography is a method or technique that contains various mathematical calculations to overcome the problem of data theft in software. Regarding the issue of data security, cloud server password security is no exception, which in this case is deliberately discussed in the Budi Darma University cloud server password security. The cryptographic method used in the Cloud Server password security research at Budi Darma University uses the Advanced Encryption Standard (AES) method which is the current standard symmetric key algorithm with a key length of 128 bits. In 128-bit AES, 1 128-bit plaintext block is first converted into a 4 x 4 hexadecimal matrix called state, each state element is 1 bit in size. The process carried out in this study is to analyze the encryption and decryption process using advanced encryption standard algorithms or what is often referred to as the Advanced Encryption Standard (AES). With this encryption method, the cloud server at Budi Darma University can be encrypted by the user into data that cannot be read by anyone so that the security and confidentiality of the data can be maintained properly and safely.